Inovasi Sistem Registrasi Digital NU (SIREGALNU) dalam Konfercab ke-XV NU Kabupaten Kebumen - Fadjeri, Akhmad; Fachri, Fahmi; Lutfiyani, Anisa; Fersellia, Fersellia; Muflih, Ghufron Zaida; Hidayat, Taufik; Nurchayati, Anisa Dwi (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Community Service Activities carried out in the Kebumen Regency NU Branch Conference process were carried out because the problems faced during the previous conference were build-up and long queues during registration, so an online-based system was created to handle this. The aim of implementing a digital registration system (SiregalNU) is to speed up implementation of registration services, digitize registration and as a digital literacy moment for NU residents in Kebumen district. This PKM activity was carried out by 15 UMNU lecturers and students. The implementation of siregalNu and the konfercab registration process were carried out for 5 days. The result of this activity is the NU digital registration system (siregalNu) which can be accessed at siregalnu.com. The main output in Siregalnu is an ID-card which has a QR code containing the unique ID of each registrant. The impact that the committee has had is having a complete database related to SK (MWC, Institution, Banom), data on participants from PRNU to MWC under the leadership of the Nahdlatul Ulama Kebumen Branch for the 2020-2024 term of office.